Analisis Pendapatan Usahatani Kakao Di Kabupaten Ende (Kajian pada Desa Kedebodu dan Rewarangga) - Imaculta Fatima (AGRICA, 2020)
One of the leading plantation commodities in Indonesia is cocoa (Theobroma Cacao). Through the Decree of the Minister of Agriculture and Plantation (Kepmentan) No.46 / Kpts / PD.300 / 2015 Ende Regency, East Nusa Tenggara [NTT] was determined as a mainstay cocoa plantation area, but in fact, the production was not optimal. Based on these considerations, this study aims to determine the level of cocoa farming income and the factors that influence farmers' income and analyze the feasibility and usefulness of a cocoa farming fund. The method used in this research is the descriptive method. The research location was determined by purposive sampling, based on the consideration that the area is a cocoa-producing region in Ende Regency. Sampling is the Ende Selatan District of Kedebodu and Rewarangga Villages. The population is all cocoa farmers, with a sample of 20 respondents. Data were collected by interview, questionnaire, observation, and documentation techniques. The feasibility analysis is done by the B / C ratio analysis. In addition to the analysis also conducted an analysis of income and receipts with the formula TC and TR. The results showed a B / C ratio of 5.24% which meant that the cocoa business was profitable and feasible to be developed. Total income from cocoa and non-cocoa is Rp 315,732,000. and from cocoa alone. Rp 91,532,000, - and total revenue of Rp. 73,897,000, and non-cocoa Rp. 29,933,000. While the total cost of cocoa is IDR 17,635,000 and non-cocoa IDR 194,267,000. Factors influencing the cocoa business in Ende District include level of education, gender participation, labor age, age of old cocoa plants, and not yet applying profitable technology. It is advisable for farmers to intensify cocoa farming by implementing P3S, and post-harvest processing, forming young people groups and building networks of cooperation with all stakeholders.